The Role of Teachers’ Psycholinguistic awareness on Second Language Teaching and Learning. [In English] - Neda Hedayat (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2020)
Psycholinguistics is concerned with how a person acquires a language, produces and perceives both spoken and written language. Moreover, Psycholinguistics is a branch of cognitive science and one of the major issues of cognitive science is “mind”. Knowing what interactions in the memory of the learner will happen when teaching foreign languages, what problems will happen in the process of memorization; memory capacity, short-term memory structure, working memory, long-term memory, semantic memory, and so on can be helpful for educators and designers of instructional books and facilitate and accelerate the process of teaching and learning foreign languages. Therefore, the aim of the present article is to overview psycholinguistic awareness and its contributions on English language learning (ELL) and English language teaching (ELT). This paper also attempts to critically and profoundly present the major research findings in the role of psycholinguistics and its implications and pedagogic contributions to the area of language learning and teaching, in an endeavor to shed light on the current successful and influential practices in this area of research which are incremental to second language learning development